2013
DOI: 10.1039/c3ra41681j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of flower-like Pd nanoparticles with high tolerance toward formic acid electrooxidation

Abstract: Flower-like nanoparticles exhibit unique properties due to the presence of edge and corner atoms, adatoms, pits and other collection of defects. In this work, flower-like Pd nanoparticles were obtained by surfactantless and additiveless square wave voltammetry as an electrochemical method of synthesis. Furthermore, other well-defined Pd shapes with dendritic growth such as spinous flower-like, cone and coral reef-like shapes were obtained by electrochemical methods using cyclic voltammetry, differential pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Change of spherical Pd particles into dendrites is further evident from the increase in intensity of (111) plane in the XRD pattern between 25 and 50 cycles of activation, which suggests that Pd particles formed on the carbon support through the reduction of PdCl 2 had grown along (111) plane forming a dendritic structure. The preferential growth direction along (111) plane for Pd dendrites has been reported in the literature by several research groups [13,28,29,36,52]. With the increase in electrochemical activation cycles to 100, the growth of dendrites were noticeable in the SEM images, whereas no significant difference was observed in the XRD patterns.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Change of spherical Pd particles into dendrites is further evident from the increase in intensity of (111) plane in the XRD pattern between 25 and 50 cycles of activation, which suggests that Pd particles formed on the carbon support through the reduction of PdCl 2 had grown along (111) plane forming a dendritic structure. The preferential growth direction along (111) plane for Pd dendrites has been reported in the literature by several research groups [13,28,29,36,52]. With the increase in electrochemical activation cycles to 100, the growth of dendrites were noticeable in the SEM images, whereas no significant difference was observed in the XRD patterns.…”
Section: Resultssupporting
confidence: 58%
“…Among various nanostructures developed, dendrites are found to play a crucial role for catalytic and electrocatalytic applications [7][8][9][10][11]. The presence of edge and corner atoms on the dendritic structures makes them advantageous in terms of reactivity than the other low-index facet-shaped, semi-spherical structures [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen adsorption/desorption region (from −0.02 to 0.23 V vs . NHE), the capacitive region (0.23 to 0.45 V) and the zone of Pd oxides formation and their respective reduction (0.45 to 1.3 V) were identified using 0.5 M H 2 SO 4 as the electrolyte . Electrochemical profiles in alkaline medium showed that the formation of Pd oxides started at −0.1 V; meanwhile, the reduction peak potential was found at −0.2 V for Pd/C IL.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 displays the CA curves of the Ag/C-5 and Ag/C-20 catalysts in 0.5M NaOH solution at 0.3V (vs. Ag/AgCl). In the first phase, it is observed that the catalysts showed a rapid current decay because of the absorbance of species on the electrode diffusion layer, and after that, it followed constant current up to the complete study of 1 hour [38,39]. The constant current with time signifies the stability of catalysts [34].…”
Section: Electrocatalytic Performances Of Ag/cmentioning
confidence: 98%